Digital libraries in Malaysia: problems faced and factors for future growth/ Norasiah Harun - Harun, Norasiah (Fakulti of Information Management, Universiti Teknologi MARA, 2011)
The article is based on the doctoral research findings from both the questionnaire (223 respondents) and interview sessions with 36 libraries (9 academic, 21 special and 6-state/public libraries). It was found that Malaysian libraries were facing various kinds of problems. Top in the list was the lack of Information Technology (IT) personnel; followed by the lack of budget, lack of digital library initiatives (DL/s) and /CT training, renewal of online subscriptions, lack of and under utilization of digital resources, and lack of suitable integrated library system. Digital library related problems were lack of staff (professional, support and IT), absence of a blueprint and National Information Infrastructure (NII) policy, digital project was too expensive which could be due to budget constrain, lack of role model and problems related to Copyright Act clearance. As the outcome of the findings, a total of eleven factors for future growth have been proposed.